Risk and Protective Factors Associated with Ovarian Cancer among Two Egyptian Cohorts - Sahar A. A. Ahmed; Sahar Yassien (Evidence-Based Nursing Research)
Context: Ovarian cancer is a global health crisis, as it is one of the devastating diagnoses for the patient and family. Nurse is a key person in the effort of health promotion, screening, and early detection. As well as care through the illness continuum.